MODEL OF HARMONIZATION OF SCIENCE AND RELIGION IN EARLY CHILDHOOD EDUCATION CURRICULUM DEVELOPMENT - Dinda Ajeng Sofiyati (Journal Informatic, Education and Management (JIEM), 2026)
The modern education system is currently confronted with the challenge of a dichotomous paradigm that separates science as a value-free, empirical-rational discipline and religion as a private, normative domain. This secular polarization impacts Early Childhood Education (ECE), which tends to be implemented partially, risking the omission of children's spiritual dimensions during their golden age. This study aims to formulate a model for harmonizing science and religion in ECE curriculum development to build a balanced intellectual, spiritual, and character growth in children. The methodology employed is descriptive qualitative with a literature study (library research) approach. Data were gathered through the documentation method from various scientific databases, including Google Scholar, Garuda, DOAJ, Scopus, and SINTA, and subsequently analyzed using content analysis techniques comprising data reduction, categorization, interpretation, and drawing conclusions. The results indicate that the harmonization of science and religion in the ECE curriculum is formulated through the integration of three main components: (1) learning objectives (balancing cognitive competence and religious character), (2) learning materials (connecting natural phenomena or STEAM learning with concrete tawhid values), and (3) learning methods (active exploration, simple experiments, and value reflection). The implementation of this conceptual model has a significant impact on children's holistic development, simultaneously covering cognitive, social-emotional, and spiritual domains. This study concludes that integrating scientific and theological aspects into the ECE curriculum serves as a crucial foundation for cultivating a generation that is academically excellent and spiritually robust.